Late-onset neonatal sepsis: Acinetobacterursingii as an infectious agent. Issue 10 (23rd October 2019) - Barros, Mariana; Garrido, Raquel; Tavares, Ana; Cunha, Manuel Sousa
Abstract : The authors report a case of a premature male newborn admitted to the neonatal intensive care unit after an emergent caesarean due to maternal pre-eclampsia and foetal bradycardia at 32 weeks of gestational age and birth weight of 1440 g. There were no infection risk factors reported. On day 3 his clinical condition deteriorated, with tachycardia and subfebrile temperature and C-reactive protein at 1.25 mg/dL. Empirical antibiotics (flucloxacillin and gentamicin) were started, with no clinical improvement and C-reactive protein increasing to a maximum of 19 mg/dL (upper normal level of 1 mg/dL) after 3 days. Blood cultures from the third to the eighth day of life were positive for Acinetobacter ursingii . Targeted therapy was administered for 14 days with clinical and laboratorial improvement and he was discharged on the 28th day of life without any known sequelae. A. ursingii is emerging as an infectious agent of late-onset sepsis in immunosuppressed neonates.